The association between early corticosteroid use and the risk of secondary infections in hospitalized patients with COVID-19: a double-edged sword. Results from the international SCCM discovery viral infection and respiratory illness universal study (VIRUS) COVID-19 registry - Bansal, Vikas; Jain, Nitesh K.; Lal, Amos; Khedr, Anwar; Tekin, Aysun; Jama, Abbas B.; Attallah, Noura; Hassan, Esraa; Mushtaq, Hisham Ahmed; Robinson, Sara; Kondori, Marjan Jahani; Koritala, Thoyaja; et al. (Frontiers in Medicine, 2025)
BackgroundCorticosteroids improve survival in hospitalized COVID-19 patients needing supplemental oxygen. However, concern exists about increased risk of secondary infections. This study investigated the impact of early corticosteroids use on these infections.MethodsData from the Society of Critical Care Medicine Discovery Viral Infection and Respiratory Illness Universal Study (VIRUS): COVID-19 registry were analyzed for adult patients, stratified by early corticosteroid use (within 48 h of admission). The primary outcome was documented secondary infections, including bacteremia, bacterial pneumonia, empyema, meningitis/encephalitis, septic shock, and ventilator-associated pneumonia. Univariate and multivariable logistic regression models were used to assess the association between early corticosteroids and these outcomes.ResultsAmong 17,092 eligible patients, with 13.5% developed at least one secondary bacterial infection during hospitalization. Patients receiving early corticosteroids were older (median 63 years) compared to those who did not (median 60 years), with a similar gender distribution (42.5% vs. 44.2% female). Unadjusted analysis revealed a higher risk for any secondary infection (OR 1.93, 95% CI 1.76–2.12). This association persisted for specific infections including bacteremia (OR 2.0, 95% CI 1.58–2.54), bacterial pneumonia (OR 1.5, 95% CI 1.27–1.77), and septic shock (OR 1.67, 95% CI 1.44–1.93). However, the effect on meningitis/encephalitis (OR 0.62, 95% CI 0.24–1.57) and ventilator-associated pneumonia (VAP; OR 1.08, 95% CI 0.75–1.57) was non-significant. Adjusted analysis maintained significance for any secondary infection (OR 1.15, 95% CI 1.02–1.29), bacteremia (OR 1.43, 95% CI 1.09–1.88), and infections with unknown sources (OR 1.63, 95% CI 1.31–2.02). Notably, the association weakened and became non-significant for bacterial pneumonia (OR 0.98, 95% CI 0.81–1.20) and septic shock (OR 0.94, 95% CI 0.79–1.11), while it became significant for meningitis/encephalitis (OR 0.26, 95% CI 0.08–0.82). VAP remained non-significant (OR 0.87, 95% CI 0.56–1.34).ConclusionEarly use of corticosteroids increased overall secondary infection risk in hospitalized COVID-19 patients, but the impact varied. Risk of bacteremia was notably increased, while the association with bacterial pneumonia and septic shock weakened after adjustment becoming non-significant and surprisingly reduced meningitis/encephalitis risk was noted suggesting the complexity of corticosteroid effects. Further research is needed to understand how corticosteroids influence specific secondary infections, and thereby optimize the treatment strategies.